Assessment of serum thiol/disulfide homeostasis in multiple myeloma patients by a new method. (2nd November 2017) - Guney, Tekin; Kanat, İlyas Ferit and Alkan, Afra and Alisik, Murat and Akinci, Sema and Silay, Kamile and Neselioglu, Salim and Dilek, Imdat and Erel, Ozcan
Abstract : Objectives: The etiology of multiple myeloma (MM) is not exactly known. This study investigated the role of thiol/disulfide homeostasis in the etiopathogenesis of MM. Methods: Some 50 patients with MM (aged 39–84 years) and 50 sex-matched healthy volunteer controls (aged 50–91 years) participated in this study. Venous blood samples were collected, and levels of native thiols, total thiols, and disulfide were measured. Results: Native and total thiol levels in the control group were determined to be higher than in the study and patient groups ( P <0.001). Disulfide levels were found to be higher in the control group than in the study group and higher in newly diagnosed patients than in outpatients who were undergoing treatment ( P =0.002). The ratios of thiol levels were found to be similar in both the study and control groups ( P >0.05). Discussion: The results of the study show that although there was a decrease in the levels of disulfide, native thiol, and total thiol, the balance of thiol/disulfide was maintained. This is the first study to research the homeostasis of dynamic thiol/disulfide from the perspective of the new method that was used. We hope that this study will encourage and facilitate further studies in this area.